(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Though all material is now available online, numerous individuals are using it; most are using it to learn things, while many others are using it to educate both how to harm or stealing information from websites or networks without such owner’s permission. The purpose of this essay is to define hacking, who programmers seem to be, what vulnerability assessment is, what ethically hacking’s code of conduct is, but also why browser hijackers are required. The Linux kernel is briefly described in detail.. All of the methods are carried out on the Kali Linux operating system. Following that, the article discusses phishing attacks and denial of service attacks (Denial of Services Attack). In addition, the paper discusses what Wi-Fi is, how to secure Wi-Fi networks, and how hackers crack Wi-Fi passwords. This paper is very useful for future work as researcher can use this paper for their survey.